Customer benefits on bitcoin as a medium of exchange / Maryam Jameelah Hashim ...[et al.] - Hashim, Maryam Jameelah; Kamarudin, Mohd Faizal; Muhamad Arifin, Nur Afizah; Khamis, Mohd Rahim (Universiti Teknologi MARA, Shah Alam, 2019)
Cryptocurrency is a digital currency that is powered by blockchain technology. One of it is bitcoin, a system that is digitally created and traded tokens to which value is assigned. The level of adoption of bitcoin has accelerated due to several fiscal crises that leads to financial crashes that have affected the lives of millions of people. This has created a demand for new kinds of niche money. Issues need to be closely discussed before it is fully accepted by customers as a medium of exchange. Even though bitcoin is used as a medium of exchange, there is still no specific guidance and benefits to the users. The issues concernedare whether the customers will get the benefits of privacy, lower transaction costs and freedom in payment. Therefore, the aims of this paper are to identify the relationship between transaction cost, privacy and digital payment as a benefit of bitcoin as a medium of exchange. This research will be conducted in Klang Valley area and the questionnaires will be disseminated directly to respondents. These respondents will be identified using probability simple random sampling. A regression analysis will be conducted comprising 200 observations in Klang Valley, Malaysia. Partial least square-structural equation (PLS-SEM) will be used. In the measurement model, reliability will be assessed by examining the Composite Reliability (CR), while validity will be assessed by convergent validity and discriminant validity. Subsequently, structural model testing with 500 re-samples was applied to test the hypothesized relationships between exogenous variables and endogenous variable. Digital payment and privacy are statistically significant towards the benefit of using bitcoin as a medium of exchange. It was found that the digital payment contributes the highest benefit to the customers followed by privacy. The results provide interesting insight into the determinants for the customers benefit using bitcoin. Although the findings show significant results customers should always decide the good and bad thoroughly before finalizing their decisions on the usage of bitcoin. Therefore, it is hoped that this study will enrich the growing literature on the subject and future research needs to explore on the benefits of using bitcoin among the real users. This study is expected to give guidelines to the policymakers on the implementation of bitcoin as a medium of exchange. It is also expected that the results may provide interesting insight into the determinants of customer benefits using bitcoin. Simultaneously, it will contribute to the elements of industry, innovation and infrastructure.